2015
DOI: 10.1128/jvi.01530-15
|View full text |Cite|
|
Sign up to set email alerts
|

The Cellular Factor NXP2/MORC3 Is a Positive Regulator of Influenza Virus Multiplication

Abstract: Transcription and replication of influenza A virus are carried out in the nuclei of infected cells in the context of viral ribonucleoproteins (RNPs). The viral polymerase responsible for these processes is a protein complex composed of the PB1, PB2, and PA proteins. We previously identified a set of polymerase-associated cellular proteins by proteomic analysis of polymerase-containing intracellular complexes expressed and purified from human cells. Here we characterize the role of NXP2/MORC3 in the infection c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…Clinically, subcutaneous edema was common in our patients and others reported with DM with anti‐NXP‐2 antibodies . Subcutaneous edema was strongly associated with vascular lesions, especially capillary damage, which led to a marked decrease in serum albumin levels . Prevalence of microinfarcts in muscle was higher in DM with subcutaneous edema , suggesting underlying vasculopathy.…”
Section: Discussionsupporting
confidence: 55%
“…Clinically, subcutaneous edema was common in our patients and others reported with DM with anti‐NXP‐2 antibodies . Subcutaneous edema was strongly associated with vascular lesions, especially capillary damage, which led to a marked decrease in serum albumin levels . Prevalence of microinfarcts in muscle was higher in DM with subcutaneous edema , suggesting underlying vasculopathy.…”
Section: Discussionsupporting
confidence: 55%
“…The H3N2 subtype NS1 protein has a histone H3K4-like sequence (histone mimic) at its carboxyl terminus that is used by the virus to target the human PAF1 transcription elongation complex, leading to suppression of hPAF1C-mediated transcriptional control of inducible antiviral gene expression (74). The NXP2/MORC3 protein, a histone reader that recognizes H3K4me3 (75), interacts with the influenza virus polymerase complex and positively modulates viral transcription (76); this protein relocalizes partially to the cytoplasm late in influenza virus infection (76). Although NXP2/MORC3, unlike the CHD1 H3K4me3 reader, is not degraded during infection, its relocalization could inhibit its still-uncharacterized nuclear function.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis of HFT cells, we found that MORC3 was detectable in only a subset of PML NBs, whereas others reported that in HeLa and Saos-2 cells MORC3 was colocalized to the majority of PML nuclear foci. This difference in detail may be due to cell type or efficiency of antibody detection, and indeed Ver et al found no significant colocalization of MORC3 with PML in A549 cells (50). One reported role of MORC3 in PML NBs is to recruit Sp100 and p53 into these complexes (12), although in the HF-derived cells used here the former function was not evident.…”
Section: Discussionmentioning
confidence: 43%
“…Our previous study identified sumoylated MORC3 as a degradation target of the HSV-1 E3 ubiquitin ligase protein ICP0 (9), which led us to further investigate the function of MORC3 during HSV-1 infection. Until now, the role of MORC3 during virus infections was relatively unknown, although one other report suggested that MORC3 was required for efficient influenza A virus (IAV) infection (50). MORC3 is a sumoylated nuclear matrix protein with RNA and DNA binding activities (13,17) that associates with PML NBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation